2004
DOI: 10.1534/genetics.104.029017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues of the Caenorhabditis elegans LIN-1 ETS Domain That Are Necessary for DNA Binding and Regulation of Vulval Cell Fates

Abstract: LIN-1 is an ETS domain protein. A receptor tyrosine kinase/Ras/mitogen-activated protein kinase signaling pathway regulates LIN-1 in the P6.p cell to induce the primary vulval cell fate during Caenorhabditis elegans development. We identified 23 lin-1 loss-of-function mutations by conducting several genetic screens. We characterized the molecular lesions in these lin-1 alleles and in several previously identified lin-1 alleles. Nine missense mutations and 10 nonsense mutations were identified. All of these lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
4
25
0
Order By: Relevance
“…VPCrep represses this basal VPCact-driven transcription in VPCs other than P6.p, thereby restricting expression of the lag-2 minimal promoter to the 1°-fated VPC. VPCrep contains an Elk1 consensus site, which is bound by LIN-1 in vitro (Miley et al 2004), and requires lin-1/Ets for repression of transcription in VPCs other than P6.p (Zhang and Greenwald 2011). Our results indicate that cdk-8 is partially required for transcriptional repression of the lag-2 minimal promoter ( Figure 4D), suggesting that the CKM promotes LIN-1-mediated repression at VPCrep.…”
Section: The Ckm Promotes Lin-1/ets Repressor Activitymentioning
confidence: 63%
“…VPCrep represses this basal VPCact-driven transcription in VPCs other than P6.p, thereby restricting expression of the lag-2 minimal promoter to the 1°-fated VPC. VPCrep contains an Elk1 consensus site, which is bound by LIN-1 in vitro (Miley et al 2004), and requires lin-1/Ets for repression of transcription in VPCs other than P6.p (Zhang and Greenwald 2011). Our results indicate that cdk-8 is partially required for transcriptional repression of the lag-2 minimal promoter ( Figure 4D), suggesting that the CKM promotes LIN-1-mediated repression at VPCrep.…”
Section: The Ckm Promotes Lin-1/ets Repressor Activitymentioning
confidence: 63%
“…VPCrep conforms to the consensus Elk1 site; LIN-1, the C. elegans Elk1 ortholog (Beitel et al 1995), has been demonstrated to bind to this consensus sequence (Miley et al 2004), suggesting that LIN-1 may mediate negative regulation Figure 2 Deletion analysis of the lag-2 promoter identified a distal element conferring P6.p-specific expression. Strains carrying independent arrays formed from the different constructs were scored for expression as indicated.…”
Section: Lin-1/elk1 and Repression Through Vpcrepmentioning
confidence: 99%
“…LIN-1 binds to the core Ets binding consensus sequence and is a direct target of phosphorylation by MPK-1/MAPK (Jacobs et al 1998(Jacobs et al , 1999Miley et al 2004). In addition, if the MAPK phosphorylation site is disrupted, LIN-1 prevents P6.p from adopting the 1°fate (Jacobs et al 1998).…”
mentioning
confidence: 99%
“…Mutations in the ETS domain that abrogate DNA binding cause a strong Muv phenotype, demonstrating that DNA binding is necessary for LIN-1 to inhibit the 1°vulval cell fate (Miley et al, 2004). LIN-1 contains two docking sites for ERK, the D domain and FQFP motif, and 17 S/TP motifs that are potential ERK phosphorylation sites (Fig.…”
Section: Introductionmentioning
confidence: 97%